Cost-effectiveness of and satisfaction with a Helicobacter pylori "test and treat'' strategy compared with prompt endoscopy in young Asians with dyspepsia - Mahadeva, S.; Chia, Y.C.; Vinothini, A.; Mohazmi, M.; Goh, K.L. (BMJ Publishing Group, 2008)
Objective: To compare a Helicobacter pylori "test and treat'' strategy with prompt endoscopy in young Asians with dyspepsia. Methods: A randomised, prospective study was carried out on uninvestigated dyspeptics aged <45 years in a single (academic) primary care centre. Patients were randomised to either a C-13 urea breath test (UBT) or prompt endoscopy (oesophagogastroduodenoscopy (OGD) and followed-up for 12 months. Results: 432 patients (mean (SD) age 30 (8) years, male 46%, ethnicity: Malays 33.3%, Chinese 30.6%, Indians 34.7%) were randomised to UBT (n = 222) or OGD (n = 210). 387 (89.6%) patients completed the study. At 12 months, there was no difference in symptom change (measured by the Leeds Dyspepsia Questionnaire) between the two groups, but more patients were very satisfied (40.0% vs 21.6%, p < 0.0001) in the OGD group. More additional endoscopy was performed in the UBT group (25 vs 10, p = 0.03), but medication consumption was higher in the OGD group (proton pump inhibitor 3.6 (8.8) vs 2.0 (7.5) weeks, p < 0.001; H2 receptor antagonist 5.3 (9.7) vs 3.9 (9.2) weeks, p = 0.017; prokinetics 1.4 (4.7) vs 0.4 (2.5) weeks, p < 0.001) and no differences in medical consultation were noted. The median cost of the initial prompt endoscopy approach at 12 months was significantly higher than a "test and treat'' strategy (US$179.05 vs US$87.10, p < 0.0001). Conclusion: A H pylori "test and treat'' strategy is more cost-effective but less satisfying than prompt endoscopy in the management of young Asian patients with uncomplicated dyspepsia.